2019
DOI: 10.5194/hess-23-4397-2019
|View full text |Cite
|
Sign up to set email alerts
|

A review of methods for measuring groundwater–surface water exchange in braided rivers

Abstract: Abstract. Braided rivers, while uncommon internationally, are significant in terms of their unique ecosystems and as vital freshwater resources at locations where they occur. With an increasing awareness of the connected nature of surface water and groundwater, there have been many studies examining groundwater–surface water exchange in various types of waterbodies, but significantly less research has been conducted in braided rivers. Thus, there is currently limited understanding of how characteristics unique… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 120 publications
0
15
0
Order By: Relevance
“…A data logger that took more than one reading per second was necessary to record a sufficient number of data points for analysis. The hydraulic conductivity values calculated from the slug tests were on the low end of the range for expected hydraulic conductivity values in this area, which may have been a reflection of the tests being conducted in localised areas of finer sediments, highlighting the limits of using this point-scale method in heterogeneous environments (Coluccio, 2018).…”
Section: Hydraulic Conductivity Testsmentioning
confidence: 92%
See 4 more Smart Citations
“…A data logger that took more than one reading per second was necessary to record a sufficient number of data points for analysis. The hydraulic conductivity values calculated from the slug tests were on the low end of the range for expected hydraulic conductivity values in this area, which may have been a reflection of the tests being conducted in localised areas of finer sediments, highlighting the limits of using this point-scale method in heterogeneous environments (Coluccio, 2018).…”
Section: Hydraulic Conductivity Testsmentioning
confidence: 92%
“…The results were compared with chemical analysis and water level measurements in the river and shallow groundwater to better inform the interpretation of the temperature data. Coluccio (2018) found that it was difficult to distinguish between shallow groundwater and hyporheic flow. The author also noted that further studies would benefit from combining a point-scale method like temperature probe analysis with broader scale techniques (Coluccio, 2018).…”
Section: Heat Tracersmentioning
confidence: 99%
See 3 more Smart Citations